Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Hasil Belajar Matematika Siswa Kelas VII Berdasarkan Level Kemampuan Matematis - Hayatun Nufus; Rezi Ariawan; Erdawati Nurdin; Hasanuddin Hasanuddin (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
This study examines the problem of improving mathematics learning outcomes among students with cooperative learning model NHT type and conventional learning approaches is reviewed as a whole and for each level of mathematical ability (high, medium, and low). This research is a quasi-experimental research design Nonequivalent Control Group Design uses Simple Random Sampling technique. The population in this study were students of class VII in a private junior high school in the city of Pekanbaru in Riau in the academic year 2014/2015. While the sample is graders VII2 as control class and class VII2 as an experimental class. The instrument used in this study is the mathematics achievement test. Quantitative analysis was performed using two mean difference test. The results showed that: (1) there is significant implementation of cooperative learning model NHT on the results of students' mathematics learning is reviewed as a whole and the level of ability was; (2) there is no effect of the application of cooperative learning model NHT towards mathematics learning outcomes of students based on high and low-level capabilities.